2015
DOI: 10.1108/nfs-06-2014-0055
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the theory of planned behavior to predict healthy eating behaviors

Abstract: Purpose – This paper aims to test whether overall and specific healthy eating behaviors and intentions could be better predicted by expanding the theory of planned behavior (TPB) to include a healthy eater identity. Major health organizations suggest increasing consumption of fruits, vegetables and whole grains to address the growing number of overweight and obese individuals, yet researchers have questioned the degree to which existing behavioral intervention programs sufficiently explain heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 32 publications
7
24
1
Order By: Relevance
“…Self-identity as healthy eater did not explain additional variance in intention to reduce consumption of red meat, consistent with Povey et al, (2001), although it has been shown to be significant for other healthy-eating behaviours (e.g., Brouwer & Mosack, 2015;Carfora, et al, 2016a). Moreover, the finding that meat-eating identity explained intentions about RMC was in line with findings of Allen and Ng (2003), which demonstrated that red meat identification had a positive correlation with RMC.…”
Section: Discussionsupporting
confidence: 72%
“…Self-identity as healthy eater did not explain additional variance in intention to reduce consumption of red meat, consistent with Povey et al, (2001), although it has been shown to be significant for other healthy-eating behaviours (e.g., Brouwer & Mosack, 2015;Carfora, et al, 2016a). Moreover, the finding that meat-eating identity explained intentions about RMC was in line with findings of Allen and Ng (2003), which demonstrated that red meat identification had a positive correlation with RMC.…”
Section: Discussionsupporting
confidence: 72%
“…Behavioral intention, in turn, is seen as a function of attitudes, subjective norms and perceived behavioral control related to that specific behavior (Ajzen, 1991). The perceived behavioral control, attitudes and subjective norms will predict intentions (Brouwer & Mosack, 2015). However, some question the degree to which the primary components of the TPB (i.e., attitudes, subjective norms, perceived behavioral control) sufficiently explain intention and behavior because the level of prediction for intention varies quite dramatically (Rise et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that those who currently eat fish perceived related past experiences more positively than those who do not (Mitterer-Daltoé et al, 2013), causing a higher fish-eating intention and, thus, consumption frequency. Likewise, consumers characterized by a healthy lifestyle will be prone to healthy diets (Brouwer & Mosack, 2015) composed of fish.…”
Section: Introductionmentioning
confidence: 99%
“…The TPB is accepted as valid and is widely used for examining any type of people's behavior [49]. It was used by numerous researchers for buying and consuming behavior explanation, for example, for predicting healthy eating behaviors [50,51], socially responsible consumption [8], and pro-environmental buying intentions, like consumers' green hotel visit intention [52].…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%